Esophageal Atresia: State of the Art in Translating Experimental Research to the Bedside - Bruns, Nicholas E.; Glenn, Ian C.; Ponsky, Todd A. (European Journal of Pediatric Surgery, 2019)
Long-gap esophageal atresia is one of the most challenging diseases in the field of pediatric surgery. There is no optimal therapy, and thus many potential therapies and techniques are being actively explored, both in animal models and in neonates. This article will review the available experimental treatment options with a focus on novel techniques.
Keywords: esophageal atresia; tracheoesophageal fistula; esophageal lengthening; esophageal replacement